Ways and mechanism of saving and increasing employment in the period of pandemics in Uzbekistan - Narmanov, Ulugbek; Ulugbek Abdugapparovich, Narmanov (CV. Inara, 2021)
The rapid spread of Covid-19 has had a negative impact on the development of the world economy, and the development of the labor market. According to the International Labor Organization, about 25 million people worldwide are unemployed worldwide and the income of employees can be reduced by at least 3.4 trillion. Therefore, the formation of the insurability of growing in the world economy and labor market on issues of stable growth and employment in Uzbekistan is relevant for today's day. The article presents information on the measures taken to mitigate the pressure rendered to the labor market caused by a pandemic in Uzbekistan.